The Use of a Storyboard Platform to Enhance Reading Comprehension: A Pedagogical Experience with EFL Pre-Service Teachers - Flora Isabel Mandiola-Villalobos; Maria Angelica Inostroza-Macaya; Danisa Thamara Salinas-Carvajal (Asociación Colombiana de Profesores de Ingles, 2024)
This study was based on an innovation project at the university level with English as a Foreign Language pre-service teachers. This experience was implemented with several language levels in different academic periods of the programme. The project aimed to apply a technological tool such as StoryboardThat, in contrast to the traditional pen-on-paper test, so that students could develop a zest for reading, allowing them to use it themselves and apply it in their teaching practices. After learning how to use the platform, they worked using a fiction novel assigned. In groups, they created three to six scenes summarizing one chapter and presented it to their peers. They stated that the project helped them improve their reading skills and inspired them to read more and use other similar platforms as an alternative in their future teaching practice. This pedagogical experience demonstrates that teachers foster a more positive attitude toward reading by integrating creativity into reading comprehension; it also equips pre-service teachers with practical tools and collaborative techniques they can apply in their future EFL teaching practice.